Impact mitigation measures for bridges under extreme flood actions. (October 2021) - Greco, F.; Lonetti, P.; Nevone Blasi, P.
Abstract: Coastal or inland bridges are affected by severe loading scenarios due to extreme flood or tsunami actions. A complete identification of the damage phenomena in infrastructure systems requires an accurate description of the fluid and structural characteristics and, specifically, of their coupling effects. In the present study, a numerical model based on a multiscale approach is developed. The structure is modeled by a 3D solid formulation, whereas the fluid domain is based on the 2D the Reynolds-averaged Navier–Stokes equations. Particular attention is devoted to the implementation of proper transfer functions going from 2D to 3D and vice versa, which take into account fluid–structure interaction, expressed in terms of bridge deformability and moving wall conditions. Several loading and wave scenarios are investigated in terms of typical fluid and structural flood parameters. The main purpose of the present study is to quantify dynamic amplification effects on the basis of formulations proposed by existing codes based on equivalent static analyses. In addition, protection or mitigation measures applied to the structural system are discussed to identify the geometry of the fairing system, which is able to reduce the effects of the wave loads in terms of applied hydraulic forces on the structure, bridge deformability and effects of damage scenarios.